2002
DOI: 10.1002/cbf.1000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arginine, ornithine and citrulline supplementation upon performance and metabolism of trained rats

Abstract: During intense exercise there is an augmented production of ammonia and IMP in the exercised muscle that could be related to the establishment of peripheral fatigue. In order to prevent this accumulation, the urea cycle in the liver eliminates ammonia in the form of urea and the skeletal muscle buffers the increase of ammonia via transamination reactions. In the present study we evaluated the effect of arginine, citrulline and ornithine supplementation, intermediates of the urea cycle, on the performance of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 24 publications
1
34
1
1
Order By: Relevance
“…Because the plasma glutamate concentration significantly increased an hour after the ingestion of L-ornithine hydrochloride and was significantly greater in the L-ornithine hydrochloride condition than that in the placebo condition immediately following and 15 min after exercise, the inhibition of ammonia concentration increase may be largely contributed to the ammonia buffering in the skeletal muscle. A difference between the results and the working hypothesis in this study was found also in the study by Meneguello et al (2003). They reported that, although a decrease in the plasma ammonia concentration and a reduction in fatigue were found, the plasma urea concentration also decreased during maximal exhaustive exercise after the ingestion of arginine, citrulline and ornithine, which are intermediates of the urea cycle, in rats.…”
Section: Discussioncontrasting
confidence: 71%
“…Because the plasma glutamate concentration significantly increased an hour after the ingestion of L-ornithine hydrochloride and was significantly greater in the L-ornithine hydrochloride condition than that in the placebo condition immediately following and 15 min after exercise, the inhibition of ammonia concentration increase may be largely contributed to the ammonia buffering in the skeletal muscle. A difference between the results and the working hypothesis in this study was found also in the study by Meneguello et al (2003). They reported that, although a decrease in the plasma ammonia concentration and a reduction in fatigue were found, the plasma urea concentration also decreased during maximal exhaustive exercise after the ingestion of arginine, citrulline and ornithine, which are intermediates of the urea cycle, in rats.…”
Section: Discussioncontrasting
confidence: 71%
“…Several previous studies have examined the antifatigue effects of amino acids that are components of the urea cycle. Meneguello et al reported that supplementation with a mixture of citrulline, arginine, and ornithine suppressed the accumulation of blood ammonia after exercise and prolonged the time to exhaustion in a swimming task by about 60% ( 11 ). Although a single supplementation of arginine or ornithine suppressed the increase in the blood level of ammonia, any effect on exercise performance was obscure (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…In a study using mice, Meneguello et al found that supplementation with a citrulline/arginine/ornithine mixture supressed the accumulation of blood ammonia after exercise and prolonged the time until exhaustion in a swimming task ( 11 ). Although arginine or ornithine supplementation is reported to suppress the accumulation of ammonia, few studies have examined whether this improves exercise performance in mice or humans (12)(13)(14).…”
mentioning
confidence: 99%
“…The concentrations of serum glucose, corticosterone, lactic acid, ammonia, and glutamine are known to serve as indicators of accumulated fatigue and stress caused by exercise. 12,[17][18][19] The analysis of these components in the blood samples collected after the last measurement of the swimming time at the sixth week of the administration showed decreases in the serum concentrations of glucose and glutamine, along with increases in the serum concentrations of corticosterone, lactic acid, and ammonia in the swimming control group compared to the non-swimming control group (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%